Transesophageal echocardiography-guided percutaneous closure of multiple muscular ventricular septal defects with pulmonary hypertension using single device: A case report - Siagian, Sisca Natalia; Prakoso, Radityo; Mendel, Brian; Hazami, Zakky; Putri, Valerinna Yogibuana Swastika; Zulfahmi,; Sakti, Damba Dwisepto Aulia; Kuncoro, Ario Soeryo (Frontiers in Cardiovascular Medicine, 2023)
Background Surgery is typically used to correct challenging ventricular septal defects (VSDs), such as VSD with pulmonary hypertension and multiple defects. In this case report, we would like to highlight the feasibility of multiple defects VSD closure with single device percutaneously using zero-fluoroscopy technique. Case presentation A 7-year-old child was referred with the main symptom of shortness of breath. She started experiencing repeated respiratory tract infections, feeding issues, and failure to thrive at the age of six months. Her body weight was only 18 kg. TEE revealed several muscular VSD with 2–3 mm and 12 mm diameters, 3 mm spacing between VSD, L to R shunt, AR (-), and TR mild with septal leaflet tricuspid prolapse. Following right heart catheterization (Qp:Qs 3.5, PVRi 5.23WUmsq, PVR 4.55 WU, PVR/SVR 0.16), we made the decision to correct the defect using an Amplatzer Septal Occluder (AGA) No. 16 mm using transjugular method. Full device deployment was successfully performed with several episodes of PVC storm and severe bradycardia. One and a half years after the procedure, her TVG dropped to only 18 mmHg, her visible indicators of PH subsided, and the PA dilator treatment was discontinued. Her body weight had increased to 28 kg, and she had no complaints. Conclusions Our experience demonstrated that percutaneous closure of multiple VSD with a single device is possible, even with pulmonary hypertension.